2015
DOI: 10.1097/nmd.0000000000000370
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Behavioral Factors Associated With Insomnia in Inpatients With Schizophrenia and Related Psychoses

Abstract: This study examines cognitive and behavioral factors linked to insomnia in individuals with schizophrenia and other psychotic disorders (with and without insomnia) and healthy controls (with and without insomnia). Fifty-five psychiatric inpatients and 66 healthy controls (n = 25 with insomnia in both groups) completed the Insomnia Severity Index, Thought Control Questionnaire for Insomnia-Revised, Dysfunctional Beliefs and Attitudes about Sleep scale, Sleep Hygiene Knowledge scale, and Beliefs about Causes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
1
21
1
2
Order By: Relevance
“…Two quantitative studies showed similar findings regarding the perceived impact of mental health and of worry. Chiu et al [ 53 ], found amongst inpatients with psychotic illnesses the most endorsed causes of sleep problems included ‘your illness’ (76%), worries and negative thoughts (72%), stress (72%), and medications (64%). Compared to community controls with insomnia participants with psychosis were ten times more likely to endorse certain biological causes (medication, illness, ‘problems with the brain’), and they were also less likely to see some lifestyle factors as affecting sleep, especially irregular sleep/wake schedule (p = 0.003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two quantitative studies showed similar findings regarding the perceived impact of mental health and of worry. Chiu et al [ 53 ], found amongst inpatients with psychotic illnesses the most endorsed causes of sleep problems included ‘your illness’ (76%), worries and negative thoughts (72%), stress (72%), and medications (64%). Compared to community controls with insomnia participants with psychosis were ten times more likely to endorse certain biological causes (medication, illness, ‘problems with the brain’), and they were also less likely to see some lifestyle factors as affecting sleep, especially irregular sleep/wake schedule (p = 0.003).…”
Section: Resultsmentioning
confidence: 99%
“…Caution should be applied in interpreting Sobieraj et al’s [ 42 ] results as it appears participants were forced to choose a single cause, whilst when given the option participants selected multiple contributing factors [ 53 ]. Collier et al’s qualitative study [ 41 ] also confirms that participants with mixed SMI perceived insomnia as interlinked with multiple other factors.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, studies which seek to understand the perspective and personal experiences of people with lived experience, in their own words, are better able to identify gaps in knowledge and define clinical targets. For instance, our recent work with groups of people with psychosis suggests that night-time rumination, worries, hallucinated voices, external locus of control ( Chiu et al, 2015a ), as well as frequent nightmares, night terrors ( Chiu et al, 2015b ) are key experiences which prevent good sleep from happening. In other words, while better sleep is an objective, targets for treatment should first address factors that get in the way of achieving this objective.…”
Section: Results Of the Qualitative Study Interviewsmentioning
confidence: 99%
“…Negative thoughts at bedtime were commonly brought up as needing coping strategies. Worries and intrusive and ruminative thoughts are a common feature of psychotic disorders ( Morrison and Baker, 2000 ) and are particularly elevated in those with symptoms of insomnia ( Chiu et al, 2015a ). It is thus particularly important that these individuals find strategies that address these psychological issues.…”
Section: Results Of the Qualitative Study Interviewsmentioning
confidence: 99%
See 1 more Smart Citation